Spectroscopy of corannulene cations in helium nanodroplets. (17th April 2019) - Gatchell, Michael; Martini, Paul; Laimer, Felix; Goulart, Marcelo; Calvo, Florent; Scheier, Paul
Abstract : We have measured the electronic spectra of corannulene cations decorated with He. Abstract : Helium tagging in action spectroscopy is an efficient method for measuring the absorption spectra of complex molecular ions with minimal perturbations to the gas phase spectra. We have used superfluid helium nanodroplets doped with corannulene to prepare cations of these molecules complexed with different numbers of He atoms. In total we identify 13 different absorption bands from corannulene cations between 5500 Å and 6000 Å. The He atoms cause a small, chemically induced redshift of the band positions of the corannulene ion. By studying this effect as a function of the number of solvating atoms we are able to identify the formation of solvation structures that are not visible in the mass spectrum. The solvation features detected using action spectroscopy agree very well with the results of atomistic modeling based on path-integral molecular dynamics simulations. By additionally doping our He droplets with D2, we produce protonated corannulene ions. The absorption spectrum of these ions differs significantly from the case of the radical cations as the numerous narrow bands are replaced by a broad absorption feature that spans nearly 2000 Å in width.